Improving the activation of peroxymonosulfate for highly efficient degradation of explosive 1, 1-diamino-2, 2-dinitroethylene through the synergetic effect of bimetallic oxides. Issue 3 (June 2022) - Zhang, Xing; Xue, Wenhua; Jia, Rui; Chen, Suhang; Liu, Enzhou; Li, Hui; Xu, Kangzhen
Abstract: The frequent use of explosives poses a potential threat to the ecological and human health, but regrettably, only a few researchers have attempted to adopt photocatalytic technology to remediate organic pollutants of explosives wastewater. Herein, a new g-C3 N4 /30%CuCo2 O4 -PMS photocatalytic system is rationally established and applied in 1, 1-diamino-2, 2-dinitroethylene (FOX-7) degradation under visible light irradiation. The effects of reaction conditions on FOX-7 degradation are explored and about 98.4% -FOX-7 can be almost completely degraded in 30 min by using 0.1 g/L catalyst and 0.1 g/L peroxymonosulfate (PMS). Quenching experiments and electron paramagnetic resonance (EPR) confirm that radical and non-radical pathways all contribute to the effective degradation of FOX-7, in which the singlet oxygen ( 1 O2 ) is the dominant reactive species. Importantly, the synchronous transformations of Cu(Ⅱ)/Cu(Ⅰ) and Co(Ⅱ)/Co(Ⅲ) valence states over CuCo2 O4 during PMS activation play an important role in the generation of reactive species. Additionally, the correspondent degradation pathways are proposed, and nitrate ions are the major degradation products. This work not only highlights the reaction mechanism of Cu-Co bimetallic oxide in the Fenton-like oxidation process, but also provides a new insight for the treatment of explosives wastewater. Graphical Abstract: ga1 Highlight: The g-C3 N4 /CuCo2 O4 -PMS system exhibited higher catalytic activity for FOX-7. Photogenerated electrons facilitated the reduction of Cu(II) and Co(III) and ROS generation. Non-radical pathways contributed more in the elimination of FOX-7. The possible degradation pathways of FOX-7 was preliminarily proposed.